Measurement of the CKM angle γ from a combination of LHCb results - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2016)
A combination of measurements sensitive to the CKM angle γ from LHCb is performed. The inputs are from analyses of time-integrated B+ → DK+, B0 → DK∗0, B0 → DK+π− and B+ → DK+π+π− tree-level decays. In addition, results from a time-dependent analysis of Bs0 → Ds∓K± decays are included. The combination yields γ = (72. 2− 7.3+ 6.8)°, where the uncertainty includes systematic effects. The 95.5% confidence level interval is determined to be γ ∈ [55.9, 85.2]°. A second combination is investigated, also including measurements from B+ → Dπ+ and B+ → Dπ+π−π+ decays, which yields compatible results.